PTEN is a protein phosphatase that targets active PTK6 and inhibits PTK6 oncogenic signaling in prostate cancer. Issue 1 (December 2017) - Wozniak, Darren; Kajdacsy-Balla, Andre; Macias, Virgilia; Ball-Kell, Susan; Zenner, Morgan; Bie, Wenjun; Tyner, Angela
Abstract PTEN activity is often lost in prostate cancer. We show that the tyrosine kinase PTK6 (BRK) is a PTEN substrate. Phosphorylation of PTK6 tyrosine 342 (PY342) promotes activation, while phosphorylation of tyrosine 447 (PY447) regulates auto-inhibition. Introduction of PTEN into a PTEN null prostate cancer cell line leads to dephosphorylation of PY342 but not PY447 and PTK6 inhibition. Conversely, PTEN knockdown promotes PTK6 activation in PTEN positive cells. Using a variety of PTEN mutant constructs, we show that protein phosphatase activity of PTEN targets PTK6, with efficiency similar to PTP1B, a phosphatase that directly dephosphorylates PTK6 Y342. Conditional disruption ofPten in the mouse prostate leads to tumorigenesis and increased phosphorylation of PTK6 Y342, and disruption ofPtk6 impairs tumorigenesis. In human prostate tumor tissue microarrays, loss of PTEN correlates with increased PTK6 PY342 and poor outcome. These data suggest PTK6 activation promotes invasive prostate cancer induced byPTEN loss. PTEN is often lost in prostate cancer. In this study, the authors show that PTEN can act as a protein phosphatase that targets active PTK6, thereby regulating its oncogenic signaling in prostate cancer progression.